Use of Atriplex canescens and Opuntia ficus indica as feed for lactating goats during drought. - Urrutia-Morales, Jorge; Gámez-Vázquez, Héctor Guillermo; Beltrán-López, Sergio; Díaz-Gómez, Marta Olivia (Agronomía Mesoamericana, 2014)
The aim of this study was to evaluate the effect of saltbush (Atriplex canescens) and prickly pear (Opuntia ficus indica) in the feeding of goats and milk production during drought. During the dry season, between May and August 2005 and between May and June 2006, three experiments were conducted in the semiarid region of San Luis Potosi, Mexico. In the first, two treatments were tested: CO) kept in confinement and controlled feeding (n = 10) and AT) kept in grazing saltbush (n = 10). In the second, two treatments were applied: AT) Atriplex (n = 5) and NP) Atriplex plus cactus (n = 5). In the third, three treatments were applied: AT) Atriplex (n = 5), NP-1,0) Atriplex plus 1,0% of cactus (n = 4) and NP-1,5) 1,5% Atriplex plus 1.5% of cactus (n = 5). In the first experiment, goats maintained their weight, but milk production was reduced to about 30% in CO and less than 8,0% in TA at the end of the experiment. In the second, goats lost weight, despite the initial milk production was less than 300 g/d. The goats fed with Atriplex reduced their production to almost half of the initial production, while the inclusion of cactus maintained production relatively stable. In the third experiment, the goats fed with Atriplex maintained their body weight, but after seven weeks milk production was only 25% of the initial production, even though it was only 300 g daily. In contrast, in the cactus supplemented goats, production tended to decrease in a lesser extent, reaching 45 and 64% of the initial production. These results are important for goat producers in the semiarid region of Mexico, where the goats could maintain good body condition, as well a production of 150 to 250 g of milk daily during the critical season using saltbush and cactus.